Could Arterial Spin Labeling Distinguish Patients in Minimally Conscious State from Patients in Vegetative State? - Wu, Bing; Yang, Yi; Zhou, Shuai; Wang, Wei; Wang, Zizhen; Hu, Gang; He, Jianghong; Wu, Xinhuai (Frontiers in Neurology, 2018)
PURPOSE: Diagnostic error is common among patients with vegetative state (VS) and minimally conscious state (MCS). The purpose of this article is to use three-dimensional pseudo-continuous arterial spin labelling (pcASL) to compare cerebral blood flow (CBF) patterns in patients in MCS with those in VS. METHODS: Patients meeting MCS and VS criteria were identified. Two post labeling delay time (PLD) pcASL on 3.0-Tesla MRI scanner system were performed with patients in the resting awake state. After registration to T1WI structure imaging, multiple brain regions of interest of ASL CBF map were automatically separated. The average CBF value of every brain region was calculated and compared between the MCS and VS groups with t tests. RESULTS: Fifteen patients with VS were identified, with ages ranging from 33 to 71 years. Eight patients who met the MCS criteria ranged in age from 23 to 61 years. Compared with VS, the regional CBF for MCS had a pattern of significantly increased CBF in the regions including the putamen, anterior cingulate gyrus, and medial frontal cortex. A left-lateralised pattern was observed to differentiate MCS from VS. CBF with PLD 2.5 s could find more regions of pattern differentiating MCS from VS than with PLD 1.5 s, except for the pallidum. CONCLUSION: MCS might be differentiated from VS by different ranges of regional CBF as measured by ASL. Multi-PLD ASL may serve as an adjunct method to separate MCS from VS and assess functional reserve in patients recovering from severe brain injuries.